Scleral buckling combined with internal cyclopexy for severe traumatic cyclodialysis cleft in open globe injuries - Chen, Bo (Int J Ophthalmol, 2019)
This study aimed to evaluate the effect of scleral buckling combined with internal cyclopexy on the treatment of severe traumatic cyclodialysis cleft in open globe injuries (OGIS). This retrospective study recruited 10 patients of 10 eyes. With our surgical intervention, all the 10 eyes achieved retinal and ciliary body anatomic re-attachment. The choroidal ruptures in nine eyes were closed with complete choroidal reattachment. Postoperative best-corrected visual acuity of nine eyes had various improvements. The mean intraocular pressure was increased from 8.9±2.6 mm Hg to 13.4±4.4 mm Hg. Eventually, six eyes underwent silicone oil (SO) removal without complications, two eyes still had SO tamponade and two eyes became SO-dependent eyes. The result shows that internal direct cyclopexy combined with scleral buckling is an effective treatment for severe traumatic cyclodialysis cleft in OGIS.